(untitled) (Law Research Review Quarterly, 2025)
There are rules governing the obligation of business actors to include the prices of goods and rates of services traded, namely regulated in Article 2 Paragraph (2) of the Regulation of the Minister of Trade No. 35/M-Dag/Per/7/2013 Concerning the Inclusion of Prices of Goods and Rates of Services Traded. The method used in this is a Qualitative Approach using the Normative Juridical research type. This study focuses on legal protection for consumers for prices of goods not listed by business actors. The results of this study are: Article 2 Paragraph (2) of the Regulation of the Minister of Trade No. 35/M-Dag/Per/7/2013 Concerning the Inclusion of Prices of Goods and Tariffs of Traded Services is not in line with higher provisions, namely the Consumer Protection Law, the weak effectiveness of law enforcement is due to the lack of socialization and supervision carried out on business actors regarding the obligation to include prices of goods and tariffs of traded services so that business actors are still found who do not include prices of traded goods and tariffs, there is legal protection for consumers for not including prices of traded goods and tariffs, namely preventive legal protection through the Community-based Consumer Protection Agency (LPKSM) such as the Semarang City Consumer Protection and Development Agency (LP2K), the Consumer Dispute Resolution Agency (BPSK) at the Central Java Province Industry and Trade Service, regarding sanctions applied to business actors, namely by imposing administrative sanctions in the form of revocation of business licenses in the field of trade carried out or repressive legal protection through a Court lawsuit in accordance with the provisions of Article 45 Paragraph (2) of the Consumer Protection Law.